Антиозонантнаактивність моно- та біметальних комплексів 3d-металів із саліцилальімінопропільними групами, іммобілізованими на нанокремнеземі - Rakyts'ka, T. L.; Truba, A. S.; Radchenko, E. O.; Golub, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
The influence of metal nature and synthesis method (joint and separate adsorption) of bimetal complexes [M1-M2-L1] based on Mn(II), Co(II), Cu(II), Zn(II) and salicylaliminopropylaerosil on their activity in ozone decomposition reaction has been studied. The activity of monometal complexes is decreased in sequence Mn(ІІ)>>Сo(ІІ)>Cu(ІІ)>Zn(ІІ) and under introduction of second metal the antiozonate properties of bimetal complexes are reduced. It is pointed out that bimetal complexes synthesized by joint sorption are more active than those prepared by means of separate adsorption of metal ions.